2018
DOI: 10.3389/fnhum.2018.00302
|View full text |Cite
|
Sign up to set email alerts
|

Empathic Neural Responses Predict Group Allegiance

Abstract: Watching another person in pain activates brain areas involved in the sensation of our own pain. Importantly, this neural mirroring is not constant; rather, it is modulated by our beliefs about their intentions, circumstances, and group allegiances. We investigated if the neural empathic response is modulated by minimally-differentiating information (e.g., a simple text label indicating another's religious belief), and if neural activity changes predict ingroups and outgroups across independent paradigms. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 48 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…A series of experiments have shown that both nausea and aversion activate similar areas of the insula, and the intensity of both activities is positively correlated with the activation of the insula. This is supported by experiments conducted by Vaughn et al (2018) on pain: there is a common mechanism for feeling an emotion and perceiving the same emotion in others. Watching another person in pain activates areas of the brain involved in the sensation of our own pain.…”
Section: How Does Imitation Create the Inner States Of Others In Our Minds?mentioning
confidence: 66%
“…A series of experiments have shown that both nausea and aversion activate similar areas of the insula, and the intensity of both activities is positively correlated with the activation of the insula. This is supported by experiments conducted by Vaughn et al (2018) on pain: there is a common mechanism for feeling an emotion and perceiving the same emotion in others. Watching another person in pain activates areas of the brain involved in the sensation of our own pain.…”
Section: How Does Imitation Create the Inner States Of Others In Our Minds?mentioning
confidence: 66%
“…Specifically, 200 ms after stimulus onset, the difference between ERP amplitudes in response to pain expressions versus neutral expressions was greater when the observer and target shared religious beliefs than when they did not. Another study showed that a single-word label presented on a hand being stabbed and indicating the person's religious affiliation (Hindu, Christian, Jewish, Muslim, Scientologist, or atheist) was enough to strongly modify the neural activity in the observer, and the direction of the effect, relative to baseline activity, was predicted by the observer's own religion (Vaughn et al, 2018). Neuro-hemodynamic responses were significantly larger when participants viewed a hand labeled with their own religion than when they viewed a hand labeled with a different religion, and the size of this bias correlated positively with the magnitude of participants' self-reported dispositional empathy.…”
Section: Responding To Human Sufferingmentioning
confidence: 99%
“…Of the three types of empathy, empathetic concern appears to be most strongly associated with observable prosocial and compassionate behavior toward others (Singer et al, 2008). Empathetic distress, or lack of it, appears to be the main component of what is popularly referred to as “unconscious bias.” That is, people tend to feel less distress or empathy-as-pain for those who they consider as being in their “out-groups” than for those who they view as being in their “in-groups” —based on any categorization of differences with others such as gender, race, age, language, socioeconomic status, or culture, to name a few (Vaughn, Savjani, Cohen, & Eagleman, 2018).…”
Section: The Three Components Of Empathymentioning
confidence: 99%
“…Some evidence suggests that collaboration with others is dependent on whether a person shares “in-group” identities. For example, the neural correlates of these responses were established in related research (Vaughn et al, 2018). Participants had their brains scanned by fMRI while they watched a needle stab hands that were labeled with different religious affiliations.…”
Section: Developing Empathy In Individuals and Organizationsmentioning
confidence: 99%